Distribution of wealth and resources in Islam: Restoring social justice, peace and prosperity - Salim, Ruhul; Hossain, M.; Al-Mawali, N. (2016)
Purpose: This paper primarily aims to investigate and discuss the underlying principles of distribution of wealth and resources in Islam. In addition, this paper also aims to derive contradictions between these principles and that of materialistic ways of acquiring wealth and resources. Design/ Methodology/Approach: Fairness and justice are fundamental virtues in Islam. With respect to fair and equitable distribution of wealth and resources in Islam this article follows the Tawhidi approach. Findings: The paradigms and guidelines set out in Qur'an regarding the creation, possession and disposition of wealth have been discussed and several contradictions are found with materialistic ways of acquiring wealth and resources. Research Limitations/ implications: As there is no Tawhidi methodology perfectly implemented in any country of the world, the proposal of this paper is still open to discussions and improvements. This paper will, hopefully, spark off quite a discussion on the topic; may result in a better understanding of the Tawhidi methodology and its operation. Practical Implications: The paper provides some ideas for implementation of Shariah principles in case of distribution of wealth and resources in order to establish peace, prosperity, justice, security and economic balance in society. Originality/Value: The paper shows its originality in substance and makes unique contribution to the literature on Tawhidisystems and ethics.